2019
DOI: 10.1101/864603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bipartite functional fractionation within the default network supports disparate forms of internally oriented cognition

Abstract: 249 words Significance: 120 words Main text: 8,344 words ORCID: 0000-0002-3009-8075 (RC); 0000-0002-4157-3409 (GFH); 0000-0001-5907-2488 (MALR) Acknowledgements:This research was funded by an MRC programme grant to MALR (MR/R023883/1) and a Sir Henry Wellcome Fellowship (201381/Z/16/Z) to RC. AbstractThe 'default network' (DN) becomes active when the mind is steered internally towards self-generated thoughts but turns dormant when the mind is directed externally towards the outside world. While hypotheses have… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 62 publications
3
17
1
Order By: Relevance
“…Our results allow us to reject accounts of the neural basis of semantic cognition that anticipate strong functional dissimilarities between DMN and MDN in all circumstances. For example, the observation that DMN tends to deactivate during demanding tasks and the deactivation is positively associated behaviour performance (Anticevic et al, 2012) has motivated the proposal that DMN is not critical for controlled cognition (Shapira-Lichter et al, 2013;Axelrod et al, 2017), or for tasks that involve attending to external inputs (even when these tasks require conceptual processing) (Chiou et al, 2020). Our findings are clearly incompatible with these views.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Our results allow us to reject accounts of the neural basis of semantic cognition that anticipate strong functional dissimilarities between DMN and MDN in all circumstances. For example, the observation that DMN tends to deactivate during demanding tasks and the deactivation is positively associated behaviour performance (Anticevic et al, 2012) has motivated the proposal that DMN is not critical for controlled cognition (Shapira-Lichter et al, 2013;Axelrod et al, 2017), or for tasks that involve attending to external inputs (even when these tasks require conceptual processing) (Chiou et al, 2020). Our findings are clearly incompatible with these views.…”
Section: Discussioncontrasting
confidence: 62%
“…A recent study found that "core" DMN regions (e.g. angular gyrus and posterior cingulate cortex) show more task-related deactivation and selective recruitment for 'internal cognition', compared with lateral temporal DMN regions implicated in semantic processing (Chiou et al, 2020). By this view, the task-negative and controlled memory accounts of DMN can be reconciled by attributing these patterns of functional recruitment to different DMN subsystems.…”
Section: Discussionmentioning
confidence: 99%
“…Other DMN regions in the core as opposed to the lateral temporal subnetwork are equally distant from sensory-motor regions along the principal gradient and yet show differences in their responsiveness to tasks. Chiou et al (2020) suggested that core DMN regions show deactivation during externallyfocussed tasks, while lateral temporal regions show engagement. We show that lateral temporal DMN activates in response to meaningful visual inputs (sentences versus letter strings), even when this input is irrelevant to the ongoing task, and irrespective of task focus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has proposed that internal cognitive states and externally oriented semantic tasks might activate distinct functional subdivisions within DMN (Andrews-Hanna et al 2010;Chiou et al 2020). Patterns of intrinsic connectivity within DMN point to separable subsystems (Andrews-Hanna et al 2010;Yeo et al 2011), focussed on (i) regions of lateral temporal cortex and anterior frontal gyrus, implicated in the representation and retrieval of conceptual knowledge (e.g., Badre and Wagner 2002;Jackson et al 2016;Lambon Ralph et al 2017), henceforth referred to as the "lateral temporal subsystem" here; (ii) medial temporal regions, such as hippocampus, that are important for episodic memory (Nyberg, McIntosh, et al 1996;Steinvorth et al 2005), termed as the "medial temporal subsystem"; and (iii) a "core" DMN subsystem drawing on posterior cingulate cortex, medial prefrontal cortex, and angular gyrus (AG), which might allow information to be transferred between these subsystems (Andrews-Hanna et al 2010;Andrews-Hanna, Smallwood, et al 2014) and which might correspond to interdigitated connectivity patterns to lateral and medial temporal subsystems (Braga and Buckner 2017;Braga et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation